Anion-Exchange Behaviour of Some Divalent Metal Ions in Nitric Acid-Organic Solvent on Amberlite IRA-410 - H. Kamal, Fatma; El-Saied, G.M.; Hassan , E.A.; Mousa, A.A. (Asian Journal of Chemistry, 2010)
The adsorbability of the bivalent metals Zn(II), Mg(II), Co(II), Ni(II), Cd(II) and Cu(II) on the strong base anion exchange resin Amberlite IRA–410 in nitrate form, from mitric acid-organic solution media were investigated. The determination of the distribution coefficients was carried out in 0.05 M–2.5 M HNO3 solution containing 0, 40, 60 and 90% (vol/vol) organic solvents. The effect of concentration of organic solvents as well as acidity on the distribution coefficient values show the importance of such media as complexing agents. Distribution coefficients were a function of both the volume percentage of organic solvents and of the nitric acid concentration. Adsorption measurements were made at constant temperature using a batch technique and employing complexometric titration and spectrophotometric analysis.